2020
DOI: 10.1186/s12885-020-07325-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel subgroup of endometrial cancer patients with loss of thyroid hormone receptor beta expression and improved survival

Abstract: Background Endometrial cancer (EC) is the most common gynecologic cancer in women, and the incidence of EC has increased by about 1% per year in the U. S over the last 10 years. Although 5-year survival rates for early-stage EC are around 80%, certain subtypes of EC that lose nuclear hormone receptor (NHR) expression are associated with poor survival rates. For example, estrogen receptor (ER)-negative EC typically harbors a worse prognosis compared to ER-positive EC. The molecular basis for the loss of NHR exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…When the expression of THRB (encoding TR beta) was tested for association with patients’ overall survival in an independent sample set, the IHC results of our cohort could be confirmed. These data are also supported by an analysis published on the TCGA cohort of endometrial cancer [ 21 ]. Applying the receptLoss algorithm, the authors highlighted that loss of THRB gene expression was linked to favorable prognosis in endometrial cancer [ 21 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When the expression of THRB (encoding TR beta) was tested for association with patients’ overall survival in an independent sample set, the IHC results of our cohort could be confirmed. These data are also supported by an analysis published on the TCGA cohort of endometrial cancer [ 21 ]. Applying the receptLoss algorithm, the authors highlighted that loss of THRB gene expression was linked to favorable prognosis in endometrial cancer [ 21 ].…”
Section: Discussionsupporting
confidence: 77%
“…These data are also supported by an analysis published on the TCGA cohort of endometrial cancer [ 21 ]. Applying the receptLoss algorithm, the authors highlighted that loss of THRB gene expression was linked to favorable prognosis in endometrial cancer [ 21 ]. In addition, TR beta mutations have been demonstrated to exert tumor-promoting activity in different types of cells [ 22 ].…”
Section: Discussionsupporting
confidence: 77%
“…In cancer, changes in circulating levels of thyroid hormones due to thyroid disease and/or altered tumour expression of their receptors may impact tumour growth, invasion, and metastatic potential, and this has been reported in several cancer types, including glioma, myeloma, breast, lung and ovarian cancer [7]. Pique and colleagues applied a novel computational tool, receptLoss, to gene expression data from The CancerGenome Atlas (TCGA) and found an association between thyroid hormone receptor beta (THRB) expression loss and increased five-year survival in women with endometrial cancer [32]. Tumours with THRB expression loss were noted to be enriched with microsatellite instable molecular subtypes of endometrial cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pique and colleagues applied a novel computational tool, receptLoss, to gene expression data from The CancerGenome Atlas (TCGA) and found an association between thyroid hormone receptor beta (THRB) expression loss and increased five-year survival in women with endometrial cancer [32]. Tumours with THRB expression loss were noted to be enriched with microsatellite instable molecular subtypes of endometrial cancer [32]. The thyroid hormone receptor beta, encoded by the THRB gene, plays a crucial role in normal development, growth, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The TH/TR axis is involved in HCC. Some studies have demonstrated that mutations of TR genes are associated with human carcinoma ( Anyetei-Anum et al, 2018 ; Piqué et al, 2020 ). A clinical study exhibited that hypothyroidism delays hepatocyte growth while hyperthyroidism promotes HCC ( Mishkin et al, 1981 ).…”
Section: Interplay Between Th/tr Axis and Liver Diseasesmentioning
confidence: 99%